Skin Exposure to Acrylates in Nail Salons. Issue 2 (1st August 2020) - Kalenge, Sheila; Kirkham, Tracy L; Nguyen, Linh V; Holness, D Linn; Arrandale, Victoria H
Abstract: Objectives: The nail salon industry has seen significant growth in recent years. Nail technicians provide manicures, pedicures and apply artificial nails; tasks that expose them to chemicals, including acrylates that are known skin and respiratory sensitizers. This paper reports on potential skin exposure to acrylates among nail technicians in Toronto, Canada. Methods: Hand skin wipes were collected after (i) the application of artificial nails, (ii) the application of ultraviolet cured gel nail polish, and (iii) deliberate contact with nail polish. Surface wipes were collected from work areas and surfaces contaminated with known products. Wipe samples were analysed for eight acrylates: methyl acrylate (MA), ethyl acrylate (EA), methyl methacrylate (MMA), ethyl methacrylate (EMA), 2-hydroxyethyl acrylate (HEA), 2-hydroxyethyl methacrylate (HEMA), 2-hydroxypropyl methacrylate (HPMA), and ethylene glycol dimethacrylate (EGDMA) by gas chromatography with mass spectrometry. Results: Thirty-five wipe samples were collected. No acrylates were detected in skin samples ( n = 8) or work surfaces ( n = 6). However, MMA, EMA, EA, HEMA, and HPMA were detected in the samples of surfaces contaminated with known products. MMA was detected in 28% of products tested. HEMA and HPMA were detected where deliberate contact with nail polish occurred. Conclusions: These results confirm that acrylates are present in nail products. However, no acrylates were detected in skin wipes. MMA, a chemical prohibited for use in cosmetics in Canada, was detected in nail polishes. Nail technicians should continue to employ safe work practices that reduce the probability of skin contact with acrylates and other chemicals.